Sustainable libraries — fashion or necessity? - Malgorzata Fedorowicz-Kruszewska (JLIS.it, 2019)
The article concerns a new libraries development strategy, which means taking account of the sustainable development concept in which the main emphasis is put on minimizing the negative influence on the natural environment, social and intergeneration justice. This organization activity concept plays more and more essential role nowadays, when there is growing natural environment devastation, social and economic anxiety and social stratification. The libraries have been interested in the idea of sustainable development since the 1990s. In the article, the sustainable library idea was presented as well as some selected examples of sustainable libraries, the appropriate tools for measuring these types of institutions and the prospects of their development.